Educational Tiktok Supporting English Vocabulary Mastery: a Case Study at MA Muhammadiyah Limpung - Risqi, Saiful; Santoso, Yan Imam; R Iswari, Ismi Islamia (Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to explore the use of TikTok content with educational value in supporting students' mastery of English vocabulary in the English Club of MA Muhammadiyah Limpung. The research uses a qualitative approach with a case study design. Data were collected through pretest–posttest tests, semi-structured interviews, and observations. Test data were analyzed descriptively to describe changes in vocabulary mastery, while qualitative data were analyzed through data reduction, data presentation, and conclusion drawn. The results showed an increase in the average score of students from a pretest of 56.4 to a posttest of 78.9. The findings of interviews and observations revealed that TikTok helps students understand the meaning of vocabulary through context, improves pronunciation through the process of imitation, and encourages the use of vocabulary in simple communication. In addition, students show a positive perception of TikTok because learning feels more relaxed and accessible, thus increasing learning engagement. However, the distraction of non-educational content and variations in content quality are obstacles that require pedagogical assistance. This study concludes that TikTok has the potential to be a supporting medium for vocabulary learning in a non-formal context if used in a targeted manner and combined with language practice activities.